Development and evaluation of a basic physical and sports activity program for preschool children in nursery schools in iran: an interventional study - Kordi, Ramin; Nourian, Ruhollah; Ghayour, Mahboubeh; Kordi, Mahboubeh; Younesian, Ali (Majallah-ʼi bīmārīhā-yi kūdakān-i Īrān = Iranian journal of pediatrics, 2012)
The objectives of this study were a) to develop a physical activity program for nursery schools, and b) to evaluate the effects of this program on fundamental movement skills of preschool age children in Iran. In this quasi-experimental study 147 children from five nursery schools in five different cities in Iran were enrolled. A physical activity program was developed for nursery children. Trained nursery physical activity instructors conducted the program for 10 weeks for all subjects. The levels of gross motor development of all subjects were measured before intervention and after 10 weeks physical activity program employing the Test of Gross Motor Development-edition 2 (TGMD-2). The participants in this study had a mean (SD) age of 4.95 (0.83) years. At the end of the study, scores of subjects at all components of TGMD-2 (including locomotor, object control, sum of standard scores and gross motor quotient) were significantly improved compared to the baseline scores (P<0.001). Based on descriptive rating of the "Gross Motor Quotient" in the base line, 11.5% of subjects were superior/very superior (GMQ >120) and after 10 weeks intervention this rate was increased to 49.7% of all subjects. It seems that the developed physical activity program conducted by trained nursery physical activity instructors could be an effective and practical way of increasing levels of fundamental movement skills of preschool children in Iran.